Investigation of Principles of Context-Sensitive Reminding - Kamar, Ece; Horvitz, Eric (Microsoft Research, 2010)
We describe research on principles of context-sensitive reminding that show promise for serving in systems that work to jog peoples’ memories about information that they may forget. The methods center on the construction and use of a set of distinct probabilistic models that predict (1) items that may be forgotten, (2) the expected relevance of the items, and (3) the cost of interruption associated with alerting about a reminder. We describe the use of this set of models in the Jogger reminder prototype that employs predictions and decision-theoretic optimization to compute the value of reminders about meetings.